Editorial Pointers. - Crawford, Diane (Communications of the ACM, 2007)
The article presents a letter from the editor of "Communications of the ACM" concerning the April 2007 issue. The issue focuses on the concept of abstraction in the computer programming industry, which can have a huge affect on a computer programmer's ability o produce clear, elegant code. Other articles discusses the technological ability of first-year college students, the strengths and weaknesses of Active Intrusion Prevention in securing computer networks, and challenges the computer industry faces in meeting customer support.